Nitrogen Addition and Warming Independently Influence the Belowground Micro-Food Web in a Temperate Steppe - Li, Qi (Public Library of Science, 2013)
Climate warming and atmospheric nitrogen (N) deposition are known to influence ecosystem structure and functioning. However, our understanding of the interactive effect of these global changes on ecosystem functioning is relatively limited, especially when it concerns the responses of soils and soil organisms. We conducted a field experiment to study the interactive effects of warming and N addition on soil food web. The experiment was established in 2006 in a temperate steppe in northern China. After three to four years (2009–2010), we found that N addition positively affected microbial biomass and negatively influenced trophic group and ecological indices of soil nematodes. However, the warming effects were less obvious, only fungal PLFA showed a decreasing trend under warming. Interestingly, the influence of N addition did not depend on warming. Structural equation modeling analysis suggested that the direct pathway between N addition and soil food web components were more important than the indirect connections through alterations in soil abiotic characters or plant growth. Nitrogen enrichment also affected the soil nematode community indirectly through changes in soil pH and PLFA. We conclude that experimental warming influenced soil food web components of the temperate steppe less than N addition, and there was little influence of warming on N addition effects under these experimental conditions.